Enhancing Student Success: Exploring Teacher Knowledge in Managing Behavior During Learning Challenges - Susanto, Ratnawati; Yulhendri, Yulhendri; Simorangkir, Sahat T; Nasution, Evi Syafrida (AL-ISHLAH: Jurnal Pendidikan, 2024)
In education, the role of teachers is one of the determining factors for student success in school. The relationship between teacher knowledge and student management with learning difficulties cannot be separated. There are still many students who do not understand the lessons given the low level of student knowledge has an impact on student independence, so research is needed to assess the current level of teacher knowledge and identify areas that need to be improved in managing the behavior of students with learning difficulties. The method used in this research is quantitative with an individual surveillance approach. The respondents were 160 people who were randomly selected at the elementary school teacher level in West Jakarta. The data collection technique uses a questionnaire containing items related to demographics and the level of knowledge of teachers as educators in managing the behavior of students with learning disabilities. All items are assessed on a Likert scale from point 1 to point 5—data analysis techniques using descriptive statistics assisted by SPSS Version 25.0. The results showed that teachers' knowledge was divided into three, namely how to manage practical behavior, positive reinforcement, and negative reinforcement, and it was found that the level of teachers' knowledge in managing practical behavior was in the high category. In conclusion, teachers' skills in managing the class can be improved by improving the management of practical behavior in the learning process to help students. The implication is that teachers who handle problematic students provide service courses and workshops related to management and provide special attention.